Images of the future of Estonian education - Paju, Kristiina (My University, 2021)
Teaching is by its core a very future-oriented profession. Teaching aims to prepare the next generation to succeed in life and to create their future. However, how well do the professional teachers consider alternative futures and understand what causes them to anticipate the future in a certain way? This study explored the futures orientation and images of the future of Estonian basic school teachers. Futures Studies methods were used to develop the participating teachers' futures literacy and to uncover their hidden assumptions regarding the future of the Estonian school by 2040. The primary research material (both individual and collaborative results) was collected from the participants of the participatory future-oriented workshop held in April 2019 in Tallinn, Estonia. The questionnaire questions were based on the Six Basic Futures Questions (Inayatullah 2008) and analyzed through the prism of will, fear, hidden assumptions, preferred futures, alternatives, next steps to elaborate on the teachers' futures thinking. The images of the future created by the two participating groups explored the probable, possible, preferable, and unpreferable futures of the Estonian school in 2040. These images of the future represent the topics teachers have encountered in their daily teaching practices or the surrounding environment. For example, the role of technology in the images of the future is sometimes controversial. In some images, it acts as an enabler. In others, as an evil dictator. The rapid technological changes cause the uncertainty of its impacts on learning and the human psyche, which are mirrored in the images of Estonian education in 2040. Both groups also created a vision for their group based on their preferred image of the future. The first group envisioned a sustainable and participatory school. The second group envisioned a future where students’ entrepreneurial skills are enhanced, and life-long learning helps students succeed in life. These visions represent the local level of visioning. They were compared to the national level vision (Smart and Active Estonia 2035) and global level vision (OECD's Vision of Education 2030) for similarities and differences. This study aimed to depict multiple images of the future of Estonian education with special attention given to developing the teachers’ futures thinking and futures literacy during the participatory future-oriented workshop.

Kuinka hyvin opettamisen ammattilaiset kuitenkin harkitsevat vaihtoehtoisia tulevai-suuksia ja ymmärtävät, mikä saa heidät ennakoimaan tulevaisuutta tietyllä tavalla? Tässä tutkimuksessa tutkittiin virolaisten peruskoulun opettajien tulevaisuuden suuntautumista ja tulevaisuudenkuvia. Tulevaisuudentutkimuksen oppimismenetelmiä käytettiin osallistuvien opettajien tulevaisuuden lukutaiton kehittämiseksi ja virolaisen koulun tulevaisuuskuvien työstämiseksi. Tutkimusmateriaali (sekä yksilölliset kyselytulokset että ryhmätyötulokset) kerättiin huhtikuussa 2019 Tallinnassa, Virossa pidetyn osallistavan tulevaisuudentyöpajan osal-listujilta. Kyselykysymykset perustuivat kuuteen tulevaisuuskysymykseen (Inayatullah 2008) ja vastauksia analysoitiin läpi tahdon, pelon, piilotettujen olettamusten, toivottujen tulevaisuuksien, vaihtoehtoisten tulevaisuuksien ja seuraavien vaiheiden prisman opettajien tulevaisuusajattelun tarkentamiseksi. Kahden osallistuvan ryhmän luomat tulevaisuuskuvat tutkivat Viron koulun todennäköisiä, mahdollisia, toivottuja ja epätoivottuja tulevaisuuksia vuonna 2040. Nämä tulevaisuuskuvat peilasivat teemoja mitä opettajat ovat kohdanneet osana jokapäiväistä opetustyötä tai yleisesti ympäristöstä. Esimerkiksi teknologian rooli tulevaisuuskuvissa on kiistanalainen. Osissa tulevaisuus-kuvissa teknologia esiintyy mahdollistajana, toisissa ilkeänä diktaattorina. Nopeisiin teknologisiin muutoksiin liittyy epävarmuus niiden vaikutuksesta. Molemmat ryhmät loivat myös vision ryhmälleen haluamansa tulevaisuuskuvan pe-rusteella. Nämä visiot edustavat paikallista visioinnin tasoa, ja niitä verrattiin sekä kan-sallisen tason (Älykäs ja Aktiivinen Viro 2035-visio) että globaalin tason (OECD: n visio koulutuksen tulevaisuudesta vuoteen 2030) visioihin yhtäläisyyksistä ja eroista. Työpajan tulosten analyysi paljasti joitain piilotettuja oletuksia, joita näillä opettajilla oli Viron koulun tulevaisuuteen liittyen. Tulevaisuuskuvat puolestaan paljastivat myös, että ne muodostuvat usein jokaisen yksilön omien ominaisuuksien sekä heidän ympäristöstään saatujen tietojen ja sosiaalisten kokemusten perusteella, jolloin tuloksena on tulevaisuuskuvat, jotka koostuvat mediasta, tutkimuspapereista ja muista tiedoista peräisin olevista tietoista ja omista kokemuksista. Tulevaisuuskuvat heijastavat myös Viron nykyaikaisen koulujärjestelmän huolestuttavia puolia (opettajien väestön harmaantuminen, resurssien ja tuen puute). Tämän tutkimuksen tarkoituksena oli korostaa opettajaväestön tulevaisuuslukutaidon merkitystä tietoisena keinona pohtia ja valmistautua vaihtoehtoisiin tulevaisuuksiin.
Keywords: Teachers, futures studies, futures literacy, Estonia, images of the future, visions, 21st-century skills